Fængslede kvinder er andet og mere end stereotyper - Charlotte Mathiassen (Nordisk Tidsskrift for Kriminalvidenskab)
Abstract In this essay, I discuss the establishment of a women’s prison in Denmark. Until recently, women have served in men’s prisons and sometimes in men’s wings. In 2018, due to questions of safety during imprisonment and ambitions of improving rehabilitative means for women, the political decision makers decided to establish a ‘women only’ facility. Among other things, I discuss the issue of imprisoned women’s rights and problematize the stereotypical representations of gender within existing prison practices.